Die virtuelle Dimension Architektur, Subjektivität und Cyberspace - Mörtenböck, Peter (2001)
Large parts of our culture are characterised by a blurring of corporeal and virtual realities. Computer industry has opened up all sorts of hybrid spaces and has itself, in turn, become a space for uncountable fantasies and expectations. Which are the principles of cultural order depicted by this desire commonly termed cyberspace? In offering novel narratives of modern architecture the author explains how the digital age couples notions of knowledge, life and future with long-known dimensions of architectonic space. Amongst the issues being discussed the reader will find Boullee's visionary designs, classical modern architecture, museums, shopping malls, science fiction, advertising, CAD, biotechnology and the construction of a utopian cyberspace at the turn of the millennium.